Current trend in biotechnology and molecular biology of fig (Ficus carica L.) - Yunus, Muhamad Fahmi; Meenakshi Sundram, Tamil Chelvan; Mohamad Hamdan, Mohd Syafik; Samsulrizal, Nurul Hidayah (Noor Publishing, 2021)
In vitro propagation offers some advantages over conventional propagation methods where it can supply uniform plants throughout the year and offer germplasm conservation. Besides, the optimization of in vitro culture conditions can accelerate and ease the research on transgenic plants through genetic engineering technology. Induced mutation breeding is a well-established method for plant improvement and this procedure can raise the possibility by a thousandfold when compared to spontaneous mutation under natural condition. Plant genetic engineering is currently a crucial method to transform genes of interest into a particular plant nuclear genome to get the desired expression. Successful transformation of fig cultivars provides a promising tool for the introduction of desired genes into fig cultivars, improved agronomic characteristic, and a means for the production of desired proteins in the edible parts of fig. Molecular markers are mostly neutral to environmental variations, in which researchers can evaluate their genetic material independently of the environmental conditions as opposed to morphological markers. Molecular markers such as RAPD, RFLP, ISSR and SSR have reportedly been prosperously utilized for the characterization of fig germplasm. Meanwhile, mutation which can occur either spontaneously or via induction plays a notable role in improving the ostiole size, fruit size, quality and productivity of fig. It is believed that fig has become one of the most valuable crops in the world as its fruits contain incredible medicinal properties and is used for the treatment of different ailments in traditional medicines.